Degree of nephrotoxicity after intermediate‐ or high‐dose cisplatin‐based chemoradiotherapy in patients with locally advanced head and neck cancer. (28th November 2015) - Driessen, Chantal M. L.; Uijen, Maike J. M.; van der Graaf, Winette T. A.; van Opstal, Claudia C. M.; Kaanders, Johannes H. A. M.; Nijenhuis, Tom; van Herpen, Carla M. L.
Abstract: Background: The purpose of this study was to compare the occurrence of cisplatin‐induced nephrotoxicity between concomitant chemoradiotherapy with high versus intermediate‐dose cisplatin. Methods: One hundred forty‐four patients with locally advanced head and neck or nasopharyngeal cancer (NPC) were included; 40 patients received cisplatin 100 mg/m 2 (high dose) on days 1, 22, and 43, and 104 patients received cisplatin 40 mg/m 2 weekly (intermediate dose) during 6 weeks in combination with radiotherapy. Results: During treatment with intermediate‐dose cisplatin, 6.7% developed an increase of ≥50% serum creatinine versus 60.0% treated with high‐dose cisplatin ( p  < .05). Nephrotoxicity (all grades) scored by Common Toxicity Criteria for Adverse Events (CTCAE) version 3.0 or CTCAE version 4.03 was 53% and 100% in the high‐dose group and 4.8% and 68% in the intermediate‐dose group, respectively. Conclusion: Significantly less nephrotoxicity occurs during chemoradiotherapy with intermediate‐dose cisplatin compared with high‐dose cisplatin. The CTCAE version 4.03 seems to be more appropriate in scoring nephrotoxicity than the CTCAE version 3.0. © 2015 Wiley Periodicals, Inc. Head Neck 38 : E1575–E1581, 2016